Scarred Lung. An Update on Radiation-Induced Pulmonary Fibrosis - Jarzebska, Natalia; Karetnikova, Ekaterina S.; Markov, Alexander G.; Kasper, Michael; Rodionov, Roman N.; Spieth, Peter M. (Frontiers in Medicine, 2021)
Radiation-induced pulmonary fibrosis is a common severe long-time complication of radiation therapy for tumours of the thorax. Current therapeutic options used in the clinic include only supportive managements strategies, such as anti-inflammatory treatment using steroids, their efficacy, however, is far from being satisfactory. Recent studies have demonstrated that the development of lung fibrosis is a dynamic and complex process, involving the release of reactive oxygen species, activation of Toll-like receptors, recruitment of inflammatory cells, excessive production of nitric oxide and production of collagen by activated myofibroblasts. In this review we summarized the current state of knowledge on the pathophysiological process leading to the development of lung fibrosis and we also discussed the possible treatment options.